Quality assessment of hydrometeorological observational data and their influence on hydrological model results in Alpine catchments. Issue 4 (12th March 2023) - Hofmeister, Florentin; Graziano, Floriana; Marcolini, Giorgia; Willems, Winfried; Disse, Markus; Chiogna, Gabriele
ABSTRACT: Hydrometeorological observational data can be affected by trends, change points and inhomogeneities. It is often difficult to identify the cause of these statistical properties of the time series and therefore they represent a source of uncertainty that can propagate to the hydrological model results. We examine two case studies of high-elevation Alpine catchments for which 59 hydrometeorological time series are analysed to show how often trends, change points and inhomogeneities in the time series occur. We consider daily and monthly aggregated data, as well as a set of nine homogeneity tests, six trend tests and three change-point tests. The results show that inhomogeneities in meteorological time series have a stronger and more direct influence on the cryosphere (snow and glacier processes) than on runoff generation. The non-linear behaviour of hydrological processes greatly complicates the judgement about the consequences of including or excluding suspicious time series in hydrological model set-ups.